Time, mourning, and pedagogy in DEVS. Issue 3 (4th March 2023) - McGill, Bonnie
ABSTRACT: The television series DEVS, written and directed by Alex Garland, and broadcast in 2020, connects to those fears around the advent of technology and certain theories in (or of) physics which undermine concepts of autonomy and free will. Through attention to the cinematic frame, I trace the appeal to a mourned reality in the 'explanatory' double-slit experiment lecture scene of the series. I focus on the ways through which a particular interpretation of what is 'seen' in the experiment is taught to create a certain narrative of reality which is already displaced. I argue that questions of a mourned reality are rehearsed in theories in (or of) physics in attempts to fix meaning in and as an object. In thinking about the impossibility of seeing another's sight, I then turn to a reading of Hugh Everett III's paper which eventually gave rise to the 'Many Worlds' interpretation of quantum mechanics. I take up again the question of who and what counts as an observer, and how claims to seeing are undermined through repeated appeals to memory and a placement of the mathematics of the theory outside of time. In a final move, I show that these questions of how to read (an object) return uncannily to the very literary questions of meaning, time and space which Jacques Derrida pursues in 'FORS'.